2014
DOI: 10.1097/qad.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for measuring rectal HIV levels suggests that HIV DNA resides in cells other than CD4+ T cells, including myeloid cells

Abstract: Summary We compared different techniques for measuring gut HIV reservoirs and assessed for HIV in non-CD4+T cells. HIV DNA levels were similar when measured from rectal biopsies and isolated rectal cells, while HIV RNA tended to be higher in rectal cells. HIV DNA levels in total rectal cells were greater than those predicted from levels in sorted CD4+T cells, suggesting a reservoir in non-CD4+T cells, and HIV DNA was detected in sorted myeloid cells (7/7 subjects).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Despite its potency to suppress HIV-1 replication, ART does not eliminate HIV-1 reservoirs, and it needs lifelong adherence to regimens that are associated with toxic effects. Although resting memory CD4 + T cells are the important HIV-1 reservoir (1), there is increasing evidence that HIV-1 exists also in other cells (2)(3)(4)(5)(6)(7). A clear demonstration that macrophages are an HIV-1 reservoir is lacking because of the difficulty in obtaining tissue samples (62).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potency to suppress HIV-1 replication, ART does not eliminate HIV-1 reservoirs, and it needs lifelong adherence to regimens that are associated with toxic effects. Although resting memory CD4 + T cells are the important HIV-1 reservoir (1), there is increasing evidence that HIV-1 exists also in other cells (2)(3)(4)(5)(6)(7). A clear demonstration that macrophages are an HIV-1 reservoir is lacking because of the difficulty in obtaining tissue samples (62).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Josefsson et al (41) found that myeloid cells isolated from the gut-associated lymphoid tissue (GALT) of HIV patients on antiretroviral therapy were positive for HIV. Yukl et al (42) observed that infected myeloid cells in the gut accounted for ϳ4% of the total HIV DNA. Moore et al (43) showed that mucosal macrophages isolated from the small intestinal mucosa of rhesus macaques either acutely or chronically infected with simian immunodeficiency virus (SIV) carried viral DNA, albeit at levels lower than memory CD4 T cells in the gut.…”
Section: The Gut Macrophage Reservoir In Hiv Infectionmentioning
confidence: 99%
“…Non-CD4 T cells harbored less HIV DNA than CD4 T cells in the gut, but the infection level of non-T leukocytes was higher in GALT than in blood (161). Myeloid cells also harbor HIV DNA in GALT (162). A recent study of patients with acute infection showed that HIV DNA in the gut was significantly lower at Fiebig stage I than at Fiebig stages II to IV (79).…”
Section: Gut-associated Lymphoid Tissuementioning
confidence: 99%